Det kristne syn på den romerske badeinstitution - Nielsen, Inge (Religionsvidenskabeligt Tidsskrift, 1993)
The christian attitude to the baths and what took place in them is clearly expressed in moral issues: with respect to the church-fathers, who are the main sources here, it seems that most aspects of life in the baths were favoured by them, for only the mixed bathing and the luxuria generally called for intervention. The position of the bath institution in urban society was also expressed by their economy. In Late Antiquity the church took over from the diminishing towns some of the large expenditures connected with the baths, but with a significant limitation: only the poor, the sick and the pilgrims were allowed in the baths built by the Church or the monasteries. Another aspect touched upon briefly is the use of the baths ritually, for instance for baptism. The development of the baths and their position in Pagan and christian society respectively is also illustrated by the buildings themselves, since a change in function and attitude is normally reflected in the architecture of the baths.